Kolmkümmend aastat udmurtide juures käimas. Mida olen õppinud? - Eva Toulouze (Mäetagused)
In my research, the Udmurt people occupy a central place. Today they are central also in my everyday life as I have paid visits to them already for 30 years because I felt that it was not enough to study only written sources and history. To understand people, their culture and mindset, you have to go to them, to see them in their everyday environment. In this article I would like to share what I have experienced when visiting them, and what I have learnt from them.